From Support to Loyalty: How Work Environment, Commitment, and Fit Affect Employee Retention - Fatmah Bagis; Efi Miftha Faridli; Mega Aprillia Pratamasar (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: This study aims to explore that how employee retention in the hotel industry is affected by a supportive work environment, organizational commitment, and person-organization fit. Methodology: Purposive sampling was used to select 162 employees from hotels and tourism destinations, and SEM-PLS was used to analyze the data. Findings: The findings demonstrated that employee retention is not directly boosted by a positive work environment. Employee retention is also positively and significantly impacted by organizational commitment and person-organization fit. This emphasizes how crucial it is to establish a work environment that encourages dedication and alignment with company values in order to boost employee retention. Implications/Novel Contribution: For real-world applications, the hospitality sector is urged to create retention plans that emphasize career advancement, leadership assistance, and raising employee engagement. The fact that this study only looked at only hospitality sector in one city of Indonesia, however, raises concerns about how generalizable the results are to other industries, such dining establishments and tourism admin- istration. It is advised that this study be expanded to include additional industrial categories in order to provide a more comprehensive knowledge.